2007
DOI: 10.1021/jo070426x
|View full text |Cite
|
Sign up to set email alerts
|

Modular One-Pot Synthesis of Tetrasubstituted Pyrroles from α-(Alkylideneamino)nitriles

Abstract: 2,3,4,5-Tetrasubstituted pyrroles have been prepared with high regioselectivity by a formal cycloaddition of alpha-(alkylideneamino)nitriles and nitroolefins followed by elimination of HCN and HNO2. The reaction allows the convergent construction of the pyrrole ring in four steps from a nitroalkane and three aldehydes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…This compound was synthesized [25] using 4-trifluoromethylbenzaldehyde (1 g, 5.7 mmol) and ammonium acetate (0.38 g, 5.0 mmol) dissolved in nitroethane (20 mL, 280 mmol), heated to 100 °C and refluxed overnight. The excess nitroethane was removed under high vacuum and the yellow mixture was poured into water (20 mL) and extracted with ethyl acetate (3 × 20 mL).…”
Section: -Trifluoromethyl-4-(nitroprop-1-enyl)benzene 13mentioning
confidence: 99%
“…This compound was synthesized [25] using 4-trifluoromethylbenzaldehyde (1 g, 5.7 mmol) and ammonium acetate (0.38 g, 5.0 mmol) dissolved in nitroethane (20 mL, 280 mmol), heated to 100 °C and refluxed overnight. The excess nitroethane was removed under high vacuum and the yellow mixture was poured into water (20 mL) and extracted with ethyl acetate (3 × 20 mL).…”
Section: -Trifluoromethyl-4-(nitroprop-1-enyl)benzene 13mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] The pioneering chemical synthesis of α-amino acids reported by Adolph Strecker in 1850 made use of their close relationship with α-aminonitriles and even today, the Strecker synthesis is still used for the industrial scale synthesis of α-amino acids like methionine. 19 Due to the strong anion stabilizing capacity of the nitrile group and the latent iminium ion reactivity, [20][21][22][23] α-aminonitriles are not only useful precursors to amino acids but also versatile building blocks for the synthesis of a wide variety of nitrogen-containing compounds 24, 25 including diverse N-heteroarenes, [26][27][28] aliphatic amine derivatives 29,30 or alkaloids [31][32][33][34][35][36][37][38][39] . We found that N-mono-and N-unsubstituted α-aminonitriles derived from aromatic or heteroaromatic aldehydes can be deprotonated quantitatively in α-position to furnish stabilized α-aminocarbanion equivalents and in contrast to their counterparts derived from aliphatic aldehydes, no N-protection is required.…”
Section: Page 1 Of 24 Acs Paragon Plus Environmentmentioning
confidence: 99%
“…It should also be mentioned that application of a-(alkylideneamino)nitriles in reactions with nitroalkenes provides a useful pyrrole synthesis, which relies on elimination of HCN and HNO 2 as the driving force for aromatization. This pathway involves a stepwise annulation mechanism rather than a cycloaddition [718]. In addition, a series of 4-hydroxypyrrole-2,3-dicarboxylates have been prepared by reactions of a-amino acids with acetylenedicarboxylates in the presence of cyclohexyl isocyanide or N,N 0 -dicyclohexylcarbodiimide as the coupling reagents [719].…”
Section: Addendummentioning
confidence: 99%